Prevalence, care-seeking behaviors and treatment cost for neonatal morbidities in Karnataka (India). Issue 2 (15th November 2019) - Golandaj, Javeed A.; Kampli, Mallikarjun S.; Hallad, Jyoti S.
Abstract : Purpose: Around three million infants die within the first four weeks of life each year – nearly all (98%) of these deaths occur in developing countries. Approximately one million newborns die each year in India. Therefore, this study aims to determine the patterns of reported neonatal morbidity and care-seeking behavior and identify factors associated with it. Design/methodology/approach: A cross-sectional study was conducted during November 2016. A systematic random sampling technique was used to select the sample. Statistical techniques like Binary Logistic regression and chi-square test were used. Findings: The results of the study showed that around 31% mothers of neonates reported that their neonates suffered from some kind of morbidity. Fever, jaundice, cough and cold, the low birth-weight and difficulty in breathing were the most common dangers signs reported. Birth order and mother's knowledge of neonatal danger signs were found to be significantly associated with reporting of neonatal morbidity. In all 95% of the mothers sought care for their newborns. Among those who had problems, 59% consulted private hospitals/clinics, 30% visited District Hospital/Taluka Hospital or higher facilities and another 9% to Primary Health Centers/Community Health Centers. Further, findings show that nearly half of the neonates taken to government facilities have got free treatment, whereas an average cost of 7, 156 INR were recorded for treatment, 935 INR for outpatient department and 13, 774 INR for inpatient department cases. Originality/value: There is an urgent need to implement intervention modalities that focus on increasing the level of parental education and access to treatment, and advocating the message regarding newborn danger signs during pregnancy is pinpointed.